Respon Pertumbuhan Dan Hasil Tanaman Padi (Oryza sativa L.) Varietas IPB 3S Pada Beberapa Sistem Jajar Legowo - Maisura, Maisura; Jamidi, Jamidi; husna, Asmaul (Agrium, 2020)
Rice is the main staple food for Indonesian people where it is cultivated in the paddy field. Considering the population growth in Indonesia is increasing, it requires an effort to increase rice production to meet the needs of the growing population. One of the efforts is through planting superior varieties such as IPB 3S with a planting system which is known as “Jajar Legowo”. This research was conducted from January to April 2018 in Puloe Iboih Village, Kuta Makmur Sub-district, North Aceh and Agroecotechnology Laboratory, Malikussaleh University. The purpose of this research is to discover the impact of the “Jajar Legowo” planting system on the growth and production of IPB 3S variety. This research used  Randomized Block Design (RBD) Non-Factorial with planting system Jajar Legowo (3:1 and 4:1) which have plant spacing 25cmx25 cm with space between plants 40 cm. These treatments had 3 replications. The results revealed that planting system Jajar Legowo significantly increased the number of tillers at 50 and 60 days after planting, plant height at 30 days after planting, the amount of chlorophyll at 60 days after planting, grain weight, yield, and harvest index. From this research, it is found that the best plant spacing in the Jajar Legowo planting system was 3:1.